A comparison of Gaussian mixture variants with application to automatic phoneme recognition - Brand, Rinus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2007.